The development of maximal running speed by means of supra maximal speed - Sedlacek, J.; Kostial, J.; Kampmiller, T.; Dremmelova, I.
This research aimed at explaining the kinematic structure changes of running on different supra maximal speed levels and on this basis at contributing for making optimal methodology of stimulus application and verifying their immediate training effect. Purpose, hypothesis, tasks, methods, procedure, results, conclusions and references are presented.